Konsep Pendidikan Menurut Ibnu Miskawaih - Farida, Nur Aini; Makbul, M (HAWARI : Jurnal Pendidikan Agama dan Keagamaan Islam, 2023)
Recently, the topic of moral or character education has received more attention in Indonesian society, particularly among academics. The events that took place reveal a lot about how moral degradation can develop. In order to build this country for a better future, global prosperity, and eternal happiness, we must look at the causes, the remedies, and the way this country is constructed. A qualitative methodology combined with a literature study method is used in this study. Greek thinkers like Plato, Zeno, and Aristotle had a significant influence on Ibn Miskawaih's ideas. In addition, he drew inspiration from Muslim philosophers like al-Kindi, al-Farabi, and ar-Razi. The purpose of education, according to Ibnu Miskawaih, is to manifest an inner attitude that is able to spontaneously encourage all actions of good value in order to obtain true and perfect happiness. Ibnu Miskawaih, who emphasizes the formation of morals by habituation, imitation, continuous imitation, and training, is in accordance with the current curriculum in Indonesia.